Enhancing accounting adoption in the Malaysian public sector: challenges and the key success factors / Agnes Paulus Jidwin … [et al.] - Paulus Jidwin, Agnes; Awang, Juliana; Ramlee, Roslida; Girau, Emelia; Ag Kee, Dgku Habibah; Ikhsan, Muhammad Izwan (Universiti Teknologi MARA, Sabah, 2023)
The transition from cash-based accounting to accrual accounting in the public sector has become a subject of growing interest globally, driven by the pursuit of improved financial transparency, accountability, and decision-making. This paper critically reviews existing literature pertaining to the challenges and success factors associated with the implementation of accrual accounting in the Malaysian public sector context. The literature review unveils a multifaceted array of challenges that hinder the seamless adoption of accrual accounting. These challenges range from the complexities of transitioning institutional structures and processes to the intricacies of aligning human resources with the demands of accrual-based financial reporting. By shedding light on the intricate dynamics of accrual accounting implementation, this paper contributes to the ongoing dialogue on strengthening financial governance, transparency, and accountability within the Malaysian public sector.